Qur'anic Parenting Patterns in the Era of Disruption: Actualizing Wahbah Az-Zuhaili's Interpretation of Q.S. Luqman 13–19 in Tafsir al-Munir - Anugrah Nur Ihsani; Achmad Abubakar; Rahmi Damis (ALSYS, 2026)
The rapid advancement of digital technology in the era of disruption has reshaped family dynamics and raised concerns about parenting crises, moral deterioration, and the weakening of spiritual bonds among young Muslims. This study aims to examine the actualization of Wahbah az-Zuhaili’s thought in Tafsir al-Munir on Q.S. Luqman verses 13–19 as a Qur’anic parenting framework responsive to the challenges of modern digital life. Employing a qualitative library research approach, the study applies thematic tafsir and content analysis to interpret the educational values embedded in these verses. The findings indicate that az-Zuhaili conceptualizes Q.S. Luqman verses 13–19 as an integrated Islamic educational framework comprising four core parenting values: tawhid as the foundation of children’s theological identity, birrul walidain as the basis of moral relations, muraqabah as divine awareness that cultivates personal integrity, and social character as a means of balancing individual piety with collective responsibility. These values are relevant and applicable as practical guidance for Muslim parents in strengthening faith-based parenting amid the complexities of digital disruption. The study concludes that Qur’anic parenting derived from az-Zuhaili’s interpretation offers a normative and practical framework for reinforcing Islamic family education, preserving children’s spiritual identity, and guiding parental roles in the contemporary digital era.